Wiara filozofów w moce sprawcze ludzkiego rozumu. Platon – Kartezjusz – Wolter (Przegląd Religioznawczy – The Religious Studies Review, 2025)
Philosophers have attempted to reconcile a faith that has its reasons in human reason with a philosophy that is the best possible confirmation of the rationality of thought and practical action. In ancient times, Plato’s attempt was one of the more significant. In modern times, Descartes and Voltaire. They provide arguments for the general thesis that, with the passage of time, the pointer in philosophy to what was attributed the greatest and positive causative power in human life shifted more and more clearly towards pointing to human reason. Were their arguments and are they convincing to others as well? This can be and is the subject of discussion. I treat my considerations as a voice in this discussion.